PENGARUH KOMPETENSI SEKRETARIS DAN SARANA PRASARANA KEARSIPAN TERHADAP MANAJEMEN ARSIP DINAMIS DI KANTOR PERPUSTAKAAN DAN KEARSIPAN DAERAH KABUPATEN BELITUNG - Chatrine Yulina Pangestu; Romulo Sinabutar (Fakultas Ekonomi Universitas Advent Indonesia, 2020)
This study aims to find out information about the competence ofsecretaries, archival infrastructure, dynamic archive management, and the influenceof secretaries' competence and infrastructure on dynamic archives management inthe offices of the Regional Library and Archives Office of Belitung Regency. Themethod used in this study is a qualitative method and descriptive method which aimsto discuss the problem of competence and infrastructure for dynamic recordsmanagement which includes aspects of organization, control and monitoring ofdynastic archives. Sources of data used by researchersutilized from journals, books,articles, web, and whatsapp. The research results show that the competenciespossessed by the Secretary or Archives Officer, Archival Facilities, and DynamicArchives Management at the Office of the Regional Library and Archives Service ofBelitung Regency have all met the standards of ANRI (National Archives of the 66Republic of Indonesia) and the system. organized work and make work moreeffective and efficient to achieve work goals.